Expression of the active human and duck hepatitis B virus polymerases in heterologous system of Pichia methanolica - Choi, J; Kim, EE; Park, JI; Han, YS (ELSEVIER SCIENCE BV, 2002)
We expressed the Hepatitis B virus polymerase (HBV P protein) using a recently introduced yeast system, Pichia methanolica. HBV (1-680 amino acids) and Duck Hepatitis B virus (DHBV, 1-780 amino acids) polymerase were expressed and showed DNA dependent DNA polymerase (DDDP). The DHBV polymerase had RNA dependent DNA polymerase (RDDP) and RNase H activities. We present a new simplified way of obtaining active viral P protein using the yeast expression system. The viral P proteins proved to be stable and were not aggregated in the yeast system. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: REVERSE-TRANSCRIPTASE ACTIVITIES; DNA-POLYMERASE; REPLICATION; YEAST; INITIATION; INHIBITION; DOMAINS; INVITRO